Slow Stroke Back Massage Intervention with Lavender Aromatherapy Oil in Pinang Room at dr. Wahidin Sudirohusodo Makassar: Case Report: Intervensi Slow Strok Back Massage dengan Minyak Aromaterapi Lavender di Ruangan Pinang di RSUP dr. Wahidin Sudirohusodo Makassar: Laporan Kasus - Gani, Nurul Fadhilah; Miftahul Janna; Hasnah; Nurhidayah (Jurnal Midwifery, 2023)
Cervical cancer is one of major cancer in women worldwide and leading causes of death. Global Cancer Observatory (Globocanl Indonesia, 2020) shows that there were 213,546 new cancer cases in 2020 and it can be further explained that 17.2% of these cancer cases are strongly influenced by early detection behavior. The most frequently reported complaint in women with cervical cancer is pain. And non-pharmacological combination therapy that is effective in dealing with pain is Slow Stroke Back Massage and lavender aromatherapy oil. Method: The case study used is a descriptive case study, with data collection techniques through assessment sheets. Data collection was carried out through interviews, physical examination, and observation. The results of the assessment and observation are explained in the nursing care format. The administration of Slow Stroke Back Massage (SSBM) intervention with lavender aromatherapy oil was carried out 1 time per day with a duration of administration, namely for 3. The procedure was carried out 4 hours after the patient took pain reliever medication. Result: Analysis of case studies in cervical cancer patients with chronic pain problems using slow stroke back massage with lavender aromatherapy oil showed that there was a decrease in pain starting from pain scale 4 to pain scale 2, measured using the "Numeric Rating Scale" pain scale instrument. Conclusion: Based on the results of the evaluation of the cases carried out, it was found that slow stroke back massage with lavender aromatherapy which lasted 10 minutes for 3 days showed that slow stroke back massage with lavender aromatherapy oil was effective in providing interventions to patients with pain problems.